2019
DOI: 10.1155/2019/1309175
|View full text |Cite
|
Sign up to set email alerts
|

Piperine Enhances the Antioxidant and Anti-Inflammatory Activities of Thymoquinone against Microcystin-LR-Induced Hepatotoxicity and Neurotoxicity in Mice

Abstract: Microcystin- (MC-) LR is the most frequent cyanotoxin produced by Microcystis aeruginosa cyanobacteria in the contaminated freshwater environment. MC represents a health hazard to humans and animals. Therefore, the present study was designed to evaluate the potential ameliorative effect of thymoquinone (TQ) and/or piperine (PP) against MC toxicity in mice. Fifty-six mice were randomly divided into seven experimental groups. Group I is the normal control that received distilled water for 21 days; Group II (TQ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 48 publications
(90 reference statements)
9
37
0
Order By: Relevance
“…Oxidative stress is a process that is initiated through well-known ROS (superoxide anion, O2 • − ; hydrogen peroxide, H 2 O 2 ; hydroxyl radical, OH • ) and reactive nitrogen species, RNS (nitric oxide, NO and peroxynitrite, ONOO − ), which are up-regulated due to exhaustion of endogenous antioxidant molecules. Subsequently, tissue damage is elicited by several mechanisms, including the promotion of lipid peroxidation (LPO), mitochondrial perturbation, DNA damage, protein nitration, and apoptotic cell death [ [36] , [37] , [38] , [39] , [40] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is a process that is initiated through well-known ROS (superoxide anion, O2 • − ; hydrogen peroxide, H 2 O 2 ; hydroxyl radical, OH • ) and reactive nitrogen species, RNS (nitric oxide, NO and peroxynitrite, ONOO − ), which are up-regulated due to exhaustion of endogenous antioxidant molecules. Subsequently, tissue damage is elicited by several mechanisms, including the promotion of lipid peroxidation (LPO), mitochondrial perturbation, DNA damage, protein nitration, and apoptotic cell death [ [36] , [37] , [38] , [39] , [40] ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that considerable quantities of OH • are produced from H 2 O 2 (by Fenton's reaction) when CAT is depleted [ 41 ]. OH • is the most harmful radical among ROS because it causes membrane damage by direct breaking down the membrane lipid content and initiating LPO and producing MDA [ 11 , 36 , 42 ]. This process was confirmed in the present study by the dramatic increase in MDA in the liver and kidney, which confirmed the occurrence of membrane damage.…”
Section: Discussionmentioning
confidence: 99%
“…TQ–piperin combination has reduced the inflammation resulting from microcystin in mice, lowering inflammatory markers (IL-1β, IL-6 and TNF-α) in the serum. The TQ–piperin combination has also decreased the oxidative damage triggered by microcystin in liver tissue and reduced malondialdehyde (MDA) and NO, while inducing glutathione (GSH) levels and superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activities [ 128 ]. Furthermore, TQ could reduce LPS-mediated inflammatory cytokine secretion, monocyte recruitment factors, and monocyte in human endothelial (HECV) cell lines.…”
Section: Antioxidant and Anti-inflammatory Activities Of Tqmentioning
confidence: 99%
“…Thymoquinone (TQ) is an 2‐methyl‐5‐isopropyl‐1, 4‐benzoquinone, which is major found in Nagalla sativa (Black cumin seed and oils) 11 . In particular, TQ are recognized to possesses a wide range of medicinal values such as anticancer, immunomodulatory, 12 antioxidant, 13 antidiabetic, 14 antiinflammatory, 15 analgesic, 16 antihypertensive, 17 gastro‐protective, 18 renal protective, 19 and anticancer 20 . Other such as derivatives from this dithyoquinone, TQ and thymol 21 .…”
Section: Introductionmentioning
confidence: 99%